Open Anterior Skull Base Reconstruction: A Contemporary Review - Kwon, Daniel; Iloreta, Alfred; Miles, Brett; Inman, Jared (Seminars in Plastic Surgery, 2017)
Skull base extirpative and reconstructive surgery has undergone significant changes due to technological and operative advances. While endoscopic resection and reconstruction will continue to advance skull base surgery for the foreseeable future, traditional open surgical approaches and reconstructive techniques are still contemporarily employed as best practices in certain tumors or patient-specific anatomical cases. Skull base surgeons should strive to maintain a working knowledge and technical skill set to manage these challenging cases where endoscopic techniques have previously failed, are insufficient from anatomical constraints, or tumor biology with margin control supersedes the more minimally invasive approach. This review focuses on the reconstructive techniques available to the open skull base surgeon as an adjunct to the endoscopic reconstructive options. Anatomic considerations, factors relating to the defect or patient, reconstructive options of nonvascular grafts, local and regional flaps, and free tissue transfer are outlined using the literature and author's experience. Future directions in virtual surgical planning and emerging technologies will continue to enhance open and endoscopic skull base surgeon's preparation, performance, and outcomes in this continually developing interdisciplinary field.
Keywords: skull base surgery; cranial base surgery; skull base reconstruction; anterior skull base; open skull base